Trophic interactions between primary consumers appear to weaken during periods of synchrony - Hooker, Katie R.; Conner, L. Mike; Jack, Steven B.; Morris, Gail; Palmer, William E.; Rutledge, Brandon T.; Sisson, D. Clay; Terhune, Theron M.; Wellendorf, Shane D.; McCleery, Robert A. (Frontiers in Ecology and Evolution, 2023)
Our understanding of synchrony between populations from different taxonomic groups has been centered on predator–prey dynamics in simple systems but has rarely been examined in complex predator–prey systems. In addition to trophic interactions such as predator–prey dynamics, there is some evidence that exogenous factor such as climatic variation may facilitate synchrony between different taxonomic groups. Using three longitudinal datasets on quail (Colinus virginianus) and cotton rats (Sigmodon hispidus) we examined 1) the consistency of synchrony across time and space, 2) the relative influence of trophic interactions vs. exogenous factors on synchrony and 3) if trophic interactions were positively associated with synchrony between populations. We found evidence of consistent synchrony in cotton rat and bobwhite populations at both the site and regional levels. We found that trophic interactions between cotton rats and bobwhite were associated with relative synchrony between these populations, but these interactions appeared to weaken in years of greater synchrony. We did not find evidence that exogenous factors influenced relative synchrony at the regional level. Given the lack of a clear mechanistic explanation of the patterns observed in our data, we propose an alternative climate-mediated predation framework to explain synchrony in complex predator–prey systems. This framework includes both classic bottom-up theories of regulation while integrating trophic interactions via components of the shared predator hypothesis.